Incorporating Character Education in ELT through Islamic Teaching Materials - Dewi Suriyani Djamdjuri; Endin Mujahidin; Nanik Retnowati; Abdul Karim Halim (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
Among the effort to provide favorable circumstances for students to study English while becoming familiar with the concepts of character values that are commonly encountered in the content of Islamic teaching materials is the incorporation of character education into English language teaching. To determine how well students are doing academically and how well they comprehend the integrated character concepts included in Islamic teaching materials, accordingly, are the goals of the current study. At one of Islamic universities in Bogor, Indonesia, this study was undertaken in the English Education Program. This research employed quasi-experimental method, and the instruments used were a test and an interview. According to the research findings, after conducting four month learning class, there is an improvement in students' achievement between pre-test and post-test in experimental groups following treatment. It indicates that Islamic materials can contribute much more to students' achievements. Furthermore, the students' understandings of integrated character values are primarily concerned with some characters: religion, honesty, independence, curiosity, friendliness, and responsibility. Students not only comprehended, but could also implement the character qualities in actual life.